Effect of Age on Complication Rates and Outcomes Following First Metatarsophalangeal Arthrodesis for Hallux Rigidus. (November 2020) - Lunati, Matthew P.; Manz, Wesley J.; Maidman, Samuel D.; Kukowski, Nathan R.; Mignemi, Danielle; Bariteau, Jason T.
Background: Hallux rigidus is one of the most common toe pathologies in patients greater than 50 years old. Although metatarsophalangeal (MTP) arthrodesis is used to improve pain and function, older patients are often considered to be higher-risk operative candidates. There are minimal data on outcomes of MTP fusion and no studies comparing outcomes between geriatric and younger patients. Methods: This is a single-center, prospective study of all patients who underwent MTP fusion between August 1, 2015, and July 1, 2018. Patient-reported outcomes were assessed using the Short Form Health Survey (SF-36), Life-Space Assessment survey (LSA), and visual analog scale (VAS) for pain administered preoperatively as well as 6 months and 1 year postoperatively. Baseline characteristics and operative outcomes were collected from the electronic medical record. Clinical and patient-reported outcomes were compared between patients <65 years old and ≥65 years old. Of 143 included patients, 79 were in the younger group (mean of 56.5 years) and 64 were in the older group (mean of 72.0 years). Results: Compared with the younger group, the older group was more predominantly female (95.3% older group, 77.2% younger group, P = .002). More patients in the older group had hypertension (73.4% older group, 50.6% younger group, P = .005) and coronary artery disease (9.4% older group, 0.0% younger group, P = .005). Both age groups had similar rates of postoperative wound complications requiring operative irrigation and debridement, deep vein thrombosis, deformity recurrence, and revision surgery. No differences were detected in SF-36, LSA, and VAS surveys administered at baseline, 6 months postoperation, or 1 year postoperation between younger and older patients. Conclusion: Despite more comorbidities, older patients had similar rates of postoperative complications and reported similar outcomes for pain, function, and mobility following MTP fusion. These findings support increased implementation of MTP fusion surgery for older patients with hallux rigidus. Level of Evidence: Level II, prospective cohort.